Pemetaan dan Analisis Sentimen E-Government pada Pemerintah Daerah di Indonesia: Mapping and Analyzing E-Government Sentiments in Local Governments in Indonesia - Joko Widodo; Kusnan Kusnan (Society, 2023)
This study aims to comprehensively map and evaluate the quality of E-Government services in local governments throughout Indonesia, focusing on public perceptions. Employing a descriptive method and qualitative approach, data collection involves non-participant observation. Researchers observed the implementation of E-Government within provincial-level local governments participating in the 2021 Electronic-Based Government Systems evaluation through Google Play. Data analysis utilizes an interactive model to provide nuanced insights. The findings reveal that E-Government implementation in Indonesian provincial governments is primarily concentrated within the E-Service category, comprising 50% or 89 applications. The most advanced category is E-Information, encompassing 38% or 67 applications. However, the E-Participation category is notably underrepresented, with only 15% or 19 applications implemented by provincial governments in Indonesia. This study contributes to a deeper understanding of Indonesia’s current landscape of E-Government services. It underscores the importance of further developments, particularly in promoting citizen participation and engagement.